The Implementation of Good Governance through Regional Inspectorate Oversight in Bone Regency - ahmad rosandi sakir (Journal of Politica Governo, 2024)
This research aims to investigate the implementation of good governance through the supervisory role carried out by the Regional Inspectorate in Bone Regency. The primary focus of this study is to provide a description and explanation of how good governance can be realized through the supervisory function of the Regional Inspectorate in Bone Regency, with a specific emphasis on establishing a governance structure free from Corruption, Collusion, and Nepotism (CCN). The research methodology used in this study is a qualitative descriptive approach. Through this method, the research seeks to identify factors influencing the implementation of good governance, including constraints and obstacles faced by the Regional Inspectorate. The results of the research indicate that the implementation of good governance in the Regional Inspectorate of Bone Regency is still not optimal. Several factors, such as limited human resources, a vast supervisory area, inadequate facilities, and a structure controlled by the regional head (Bupati Bone), impact the effectiveness of supervision. The study also highlights the importance of establishing a governance structure free from CCN as an integral part of the goal to improve governance. In conclusion, efforts to achieve good governance in Bone Regency through the Regional Inspectorate require attention to these factors. Improvements in human resources, infrastructure, and organizational structure can enhance the effectiveness of supervision and support the establishment of a clean and efficient governance structure